Long alkylchain iminosugars block the HCV p7 ion channel - Pavlovic, D; Fischer, W; Hussey, M; Durantel, D; Durantel, S; Branza-Nichita, N; Woodhouse, S; Dwek, R; Zitzmann, N (Springer Verlag, 2005)
The small p7 protein of the hepatitis C virus (HCV) and the closely related bovine viral diarrhea virus (BVDV) can form ion channels in artificial membranes Ion channel activity can be suppressed by long alkylchain iminosugar derivatives, which have been shown to be antiviral in BVDV infectivityassays. Treatment with these inhibitors does not affect viral RNA replication. However, the infectivity ff of virions secreted in the presence of the inhibitors is impaired. The physiological role of the p7 ion channel during the virallife cycle is unknown and is being investigated using inhibitory iminosugars as well as a BVDV construct from which p7 has been deleted.